Antihypertensive Medications and the Survival Rate of Osseointegrated Dental Implants: A Cohort Study. (3rd March 2016) - Wu, Xixi; Al‐Abedalla, Khadijeh; Eimar, Hazem; Arekunnath Madathil, Sreenath; Abi‐Nader, Samer; Daniel, Nach G.; Nicolau, Belinda; Tamimi, Faleh
Abstract: Purpose: Antihypertensive drugs in general are beneficial for bone formation and remodeling, and are associated with lower risk of bone fractures. As osseointegration is influenced by bone metabolism, this study aimed to investigate the association between antihypertensive drugs and the survival rate of osseointegrated implants. Materials and Methods: This retrospective cohort study included a total of 1, 499 dental implants in 728 patients (327 implants in 142 antihypertensive‐drugs‐users and 1, 172 in 586 nonusers). Multilevel mixed effects parametric survival analyses were used to test the association between antihypertensive drugs use and implant failure adjusting for potential confounders. Results: Only 0.6% of the implants failed in patients using antihypertensive drugs while 4.1% failed in nonusers. A higher survival rate of dental implants was observed among users of antihypertensive drugs [HR (95% CI): 0.12 (0.03–0.49)] compared to nonusers. Conclusions: Our findings suggest that treatment with antihypertensive drugs may be associated with an increased survival rate of osseointegrated implants. To our knowledge, this could be the first study showing that the systemic use of a medication could be associated with higher survival rate of dental implants.